Damage tolerance enhancement of thermoset composites modified with thermoplastic veil interleaves - Ramji, Amit (Cranfield University, 2019)
A feasible method of overcoming the stringent certification and ecological sustainability objectives within the aerospace sector is to substitute conventional engineering alloys with high-performance lightweight composite materials for primary structures. Although, widespread utilisation of laminated composites are constrained by the significant reduction of the residual compressive strength stemming from a lack of through-thickness reinforcement leading to interface delamination. This work presents the detailed investigations on the characteristics of the fibre-matrix interactions in conjunction with ply interface enhancements; to develop new knowledge for damage tolerance enhancement of thermoset composite laminates modified with thermoplastic veil interleaves. The influence of fracture initiation and propagation is the focus of this work, through the experimental exploration of various failure mechanisms. The failures of toughened carbon-fibre/epoxy laminates with poly-phenylene sulfide (PPS) veil interlayers are considered under; inter-laminar, intra-laminar, fracture migration and low-velocity impact damage. Conservative test standards for the interlaminar fracture resistance present veil interleaves as having a 48% enhancement on the interlaminar fracture parameters for longitudinal propagation of unidirectional (UD) fibre reinforced polymer (FRP) laminates. However, interleaving enhancements are revealed to be over-projected when fracture propagation is transverse to the interfacial fibre orientation with enhancements being <2%. Under mode I loading, intra-laminar fracture plane migration is the dominant damage mechanism for transverse yarn interfaces, which trigger migration away from the toughened interface. In contrast, woven lamina cannot permit through-thickness migration due to yarn interlacing, where 136% for longitudinal bias and 20% for transverse biased enhancements are apparent using 20 gm-2 PPS. Furthermore, reductions of interfacial fibre orientation bias sensitivity were demonstrated for veil interleaved interfaces. Similarly, under mode II loading, transverse biased interfaces exhibited up to 75% improvement in delamination resistance with gradual growth characteristics resulting from the veil and transverse fibre interactions. Interleaved laminates were subsequently explored for low-velocity impact damage, emphasising on veil distributions within the laminate. Interleaving the outside interfaces transformed the damage from inter-laminar to intra-laminar and increased the delamination threshold load (DTL) by 9% or entirely removed DTL occurrences for heavily interleaved layups. The veil damage mechanisms resulting in improved fracture resistance and enhanced damage tolerance are due to the inclusion of lower modulus PPS fibres. These discrete thermoplastic regions within the laminate provide a cushioning effect while increasing the localised ductility resulting in increased fibrematrix interactions at the fracture process zone.
Keywords: Carbon fibre composite; Damage tolerance enhancement; Delamination damage mechanics; Fibre bridging; Fracture toughness; Impact behaviour; Interphase; Matrix cracking; Non-woven Nano veils; Veil interleave toughening